Implementation of Restorative Justice in the Settlement of Traffic Cases with Minor Injury Victims in Wonogiri - Kurnianingsih, Marisa; Pradana, Aditya Bayu (Universitas Muhammadiyah Surakarta, 2024)
Artikel ini disusun untuk mengetahui implemtasi restorative justice dalam penyeelsaian perkara lalu lintas dengan korban luka ringan di Wonogiri. Wonogiri adalah salah satu wilayah di Indonesia yang setiap tahun memiliki tingkat kecelakaan yang tinggi setiap tahunnya yang mayoritas terjadi pada pengendara kendaraan roda dua. Artikel ini disusun dengan menggunakan metode pendekatan yuridis empiris dimana fakta di lapangan terkait dengan restorative justice dalam perkara lalu lintas disandingkan dengan peraturan yang berlaku. Pemicu terjadinya kecelakaan lalu lintas ini salah satunya yaitu kelalaian pengendara sehingga kecelakaanpun tidak dapat dihindarkan. Restorative justice di Wonogiri sering digunakan khususnya dalam perkara lalu lintas dengan korban luka ringan dan masih terdapat hambatan-hambatan dalam pelaksanaanya. The high frequency of traffic accidents in Wonogiri, particularly those involving motorcycle riders, has become a significant concern. Each year, a considerable number of these incidents result in minor injuries, highlighting the need for an effective and humane approach to case resolution. This article explores the implementation of restorative justice in resolving traffic cases with minor injury victims in Wonogiri. The research aims to assess how restorative justice is applied in these cases and to identify the challenges that may hinder its effective implementation. The study employs an empirical juridical methodology, where real-world practices of restorative justice in traffic accident cases are compared with the applicable legal regulations in Indonesia. Data was gathered through field research, including interviews with law enforcement, judicial officials, and the parties involved in traffic cases. The empirical approach allows for a comprehensive understanding of how restorative justice is practiced in Wonogiri, focusing on its effectiveness and any obstacles encountered during its application. The findings reveal that restorative justice is frequently utilized in traffic cases with minor injuries in Wonogiri. This approach is valued for its ability to facilitate reconciliation between the victim and the offender, often leading to more satisfactory outcomes for both parties compared to conventional legal proceedings. However, the study also identifies several challenges, such as inconsistencies in its application and a lack of awareness and training among those responsible for implementing restorative justice. The research concludes that while restorative justice offers significant potential for resolving traffic cases in Wonogiri, addressing these challenges is crucial to improving its effectiveness. The study recommends the development of clearer guidelines, enhanced training for law enforcement and judicial personnel, and increased public awareness to support the broader implementation of restorative justice in traffic case resolutions.